Mato Grosso e suas ações no cenário internacional (1995-2010) - Gatto, Luis Henrique Soares (2012)
The accentuated globalization process post Cold War, associate with a stronger Brazilian presence in international trade, propitiate to the Federation Units (states or counties) significant expansion of its international integration processes. Due this phenomenon some theoretical approaches in International Relations suggest the hypothesis that the federal units have acquired greater autonomy for external action. This thesis focuses on the analysis of the international actions of the State of Mato Grosso (MT) from the reality that being one of the Federation Units leading export; the absence of literature analyzing their external actions and by the fact bordering with Bolivia, a situation that provides several exchanges experiences. Thus, we intend to reflect about the existence of autonomy to a Federation s entity prepare their external actions, whither this autonomy will, and, within this perspective, such Mato Grosso is positioned in relation to their integration into the international scene and to engage this quest